2008
DOI: 10.1007/s00421-008-0901-9
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mitochondrial respiration by inorganic phosphate; comparing permeabilized muscle fibers and isolated mitochondria prepared from type-1 and type-2 rat skeletal muscle

Abstract: ADP is generally accepted as a key regulator of oxygen consumption both in isolated mitochondria and in permeabilized fibers from skeletal muscle. The present study explored inorganic phosphate in a similar regulatory role. Saponin permeabilized fibers and isolated mitochondria from type-I and type-II muscle from male Wistar rats were prepared. Respiration was measured while the medium P(i) concentration was gradually increased. The apparent K(m) values for P(i) were 607 +/- 17 microM and 405 +/- 15 microM (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 50 publications
4
20
0
Order By: Relevance
“…The baseline value of RCR in the present study was ϳ4, similar to previously reported values with permeabilized fibers in man and rat (8,51), albeit lower than what is usually found in isolated mitochondria from similar rat muscles (19). We found a pronounced increase (ϳ50%) in RCR after 6 mo of high-fat diet, and this increase showed a tendency to be higher in the groups that have also been exposed to maternal caloric restriction (Table 2).…”
Section: Postnatal High-fat Dietsupporting
confidence: 79%
See 1 more Smart Citation
“…The baseline value of RCR in the present study was ϳ4, similar to previously reported values with permeabilized fibers in man and rat (8,51), albeit lower than what is usually found in isolated mitochondria from similar rat muscles (19). We found a pronounced increase (ϳ50%) in RCR after 6 mo of high-fat diet, and this increase showed a tendency to be higher in the groups that have also been exposed to maternal caloric restriction (Table 2).…”
Section: Postnatal High-fat Dietsupporting
confidence: 79%
“…Mitochondrial function was tested in Oroboros Oxygraph-2K instruments (Oroboros, Innsbruck, Austria), operating six oxygraph chambers in parallel at 25°C (51). Approximately 2.5 mg of permeabilized fibers was added to 2 ml of medium in each chamber.…”
Section: Mitochondrial Functionmentioning
confidence: 99%
“…Whether this occurs in skeletal muscle has yet to be established. These functional results combined with the proteomic data above and previous findings that the K m values for both ADP and P i are no different between mitochondria isolated from red and white muscle (36,44) suggest that many of the acute regulatory mechanisms within these mitochondria are also similarly poised when isolated from resting muscle. This similarity in protein content and activity level per mole enzyme, for those we queried, suggest that the configuration of mitochondria in these two muscle types is nearly identical to produce ATP as a function of mitochondrial volume.…”
Section: Discussionsupporting
confidence: 67%
“…Increased ADP and Pi, which are produced during ATP hydrolysis at muscle cross-bridges and other cellular processes like Ca 2ϩ pumping, are potent activators of mitochondrial respiration (19,37). In the current study, as isometric tension and ATP hydrolysis decline with reduced cross-bridge turnover and reduced Ca 2ϩ pumping during fatigue, this could explain the fall in respiration in FF fibers.…”
Section: Discussionmentioning
confidence: 72%